Synergy on particulate matter emission during the combustion of bio-oil/biochar slurry (bioslurry) - Feng, C.; Wu, Hongwei (Elsevier Ltd, 2018)
© 2017 Elsevier Ltd Bio-oil/biochar slurry (i.e. bioslurry) is a new type of fuel that is prepared by suspending fine biochar particles into fast pyrolysis bio-oil. This study reports the synergy on PM 10 emission during bioslurry combustion in a laboratory-scale drop-tube-furnace in air at 1400 °C. The experimental results show that the PM 10 emission from the direct combustion of bioslurry (with 5 or 10% biochar loading level) is higher than the sum of those from separate bio-oil and biochar combustion, clearly indicating the existence of synergy. It is evident that at least two mechanisms are responsible for such synergistic effects. One mechanism is the leaching of inorganic species from biochar by acidic bio-oil in the bioslurry system. This is demonstrated by the direct comparisons between PM 10 emissions from the combustion of bio-oil or biochar before and after bioslurry preparation. The experimental results show that such a leaching effect leads to both an increase in PM 1 and a decrease in PM 1–10 during combustion, because of the redistribution of inorganic species between the bio-oil and biochar fractions of bioslurry. The other mechanism is the synergy between the bio-oil and biochar fractions that takes place during bioslurry combustion. This is demonstrated by the comparison between PM 10 emissions from the direct bioslurry combustion and the sum of PM 10 from the separate combustion of bio-oil and biochar fractions separated from bioslurry. The interactions between the combustions of bio-oil and biochar fractions lead to an increase in PM 1 and a decrease in PM 1–10 during bioslurry combustion. The results further show that the second mechanism (i.e. interactions between the combustions of bio-oil and biochar fractions) accounts for ~ 80% of the total increase in PM 1 and ~ 60% of the total decrease in PM 1–10 .